2013
DOI: 10.1016/j.freeradbiomed.2012.08.574
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns are associated with plasma F2-isoprostanes in an observational cohort study of adults

Abstract: Associations between individual foods or nutrients and oxidative markers have been reported. Comprehensive measures of food intake may be uniquely informative, given the complexity of oxidative systems and the possibility for antioxidant synergies. We quantified associations over a 20 y history between 3 food-based dietary patterns, summary measures of whole diet, and a plasma biomarker of lipid peroxidation, F2-isoprostanes in a cohort of Americans, aged 18–30 at year 0 (1985–86). We assessed diet at years 0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
90
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(97 citation statements)
references
References 35 publications
7
90
0
Order By: Relevance
“…As appropriate to a study of adolescents, our dietary pattern did not include alcoholic items, unlike the adult version of the APDQS. The limited published data available linking the APDQS with BMI during young-to-mid adulthood are in accordance with our findings (13, 32). …”
Section: Discussionsupporting
confidence: 93%
“…As appropriate to a study of adolescents, our dietary pattern did not include alcoholic items, unlike the adult version of the APDQS. The limited published data available linking the APDQS with BMI during young-to-mid adulthood are in accordance with our findings (13, 32). …”
Section: Discussionsupporting
confidence: 93%
“…The results from several placebo-controlled, randomized clinical trials (RCTs) of the effects of limited numbers of supplemental antioxidant micronutrients on FIP have been inconsistent (Dietrich et al, 2002, Gokce et al, 1999, Patrignani et al, 2000). However, when nutrients were examined in combination as a dietary score (similarly as for the OBS) in observational studies, stronger associations with FIP were observed (Meyer et al, 2013). In the Coronary Artery Risk Development in Young Adults (CARDIA) study, a diet quality score was determined by assigning higher points to frequent consumption of foods beneficial to health, and lower points to frequent consumption of foods believed to be detrimental to health (all determined a priori ) (Meyer et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, when nutrients were examined in combination as a dietary score (similarly as for the OBS) in observational studies, stronger associations with FIP were observed (Meyer et al, 2013). In the Coronary Artery Risk Development in Young Adults (CARDIA) study, a diet quality score was determined by assigning higher points to frequent consumption of foods beneficial to health, and lower points to frequent consumption of foods believed to be detrimental to health (all determined a priori ) (Meyer et al, 2013). A significant inverse association was observed between the dietary score and plasma FIP (Meyer et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…both healthy and unhealthy food groups (8). In the Iowa Women's Health Study, this a priori diet quality score is associated with lower total, CVD, and cancer mortality (42).…”
Section: Discussionmentioning
confidence: 99%
“…Food-based scores are easier to adapt for clinical use because they do not require software or a database to perform nutrient analysis. Several food-based dietary quality scores have been associated with CVD risk factors such as inflammatory markers and fasting insulin (8)(9)(10). Only 2 food-based scores have been examined for CVD endpoints.…”
Section: Introductionmentioning
confidence: 99%